2019
DOI: 10.30773/pi.2019.0226
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Patient Health Questionnaire-9 in a Sample of Korean University Students

Abstract: In South Korea (hereafter Korea), mental-health problems have become an important national issue. Korea's public health authority has focused heavily on mental health, particularly depression, due to the country's consistently high suicide rate relative to other Organization for Economic Cooperation and Development (OECD) member nations. 5 In fact, Korea has had the highest suicide rate among OECD countries in annual rankings more than 10 times since 2003. 6 Korea's suicide rate of 29.1 per 100,000 people in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 32 publications
9
49
4
Order By: Relevance
“…The unidimensionality and Cronbach alpha coefficients of the GAD-7 found in this study are congruent with studies conducted in other populations. For example, this study had strikingly analogous findings to those reported for Korean and Portuguese university students (Bartolo et al, 2017;Lee and Kim, 2019). Similar findings also were reported for primary care patients (Jordan et al, 2017;Johnson et al, 2019), psychiatric patients (Dear et al, 2011;Kertz et al, 2013;Konkan et al, 2013;Rutter and Brown, 2017;Johnson et al, 2019), infertility patients (Omani-Samani et al, 2018), the general population in several countries (Konkan et al, 2013;Sousa et al, 2015;Hinz et al, 2017), adolescents (Tiirikainen et al, 2019), individuals receiving care in a traditional medicine department in China (Zeng et al, 2013), and in non-English speakers (Mills et al, 2014;Sousa et al, 2015;Ahmad et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The unidimensionality and Cronbach alpha coefficients of the GAD-7 found in this study are congruent with studies conducted in other populations. For example, this study had strikingly analogous findings to those reported for Korean and Portuguese university students (Bartolo et al, 2017;Lee and Kim, 2019). Similar findings also were reported for primary care patients (Jordan et al, 2017;Johnson et al, 2019), psychiatric patients (Dear et al, 2011;Kertz et al, 2013;Konkan et al, 2013;Rutter and Brown, 2017;Johnson et al, 2019), infertility patients (Omani-Samani et al, 2018), the general population in several countries (Konkan et al, 2013;Sousa et al, 2015;Hinz et al, 2017), adolescents (Tiirikainen et al, 2019), individuals receiving care in a traditional medicine department in China (Zeng et al, 2013), and in non-English speakers (Mills et al, 2014;Sousa et al, 2015;Ahmad et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings also were reported for primary care patients (Jordan et al, 2017;Johnson et al, 2019), psychiatric patients (Dear et al, 2011;Kertz et al, 2013;Konkan et al, 2013;Rutter and Brown, 2017;Johnson et al, 2019), infertility patients (Omani-Samani et al, 2018), the general population in several countries (Konkan et al, 2013;Sousa et al, 2015;Hinz et al, 2017), adolescents (Tiirikainen et al, 2019), individuals receiving care in a traditional medicine department in China (Zeng et al, 2013), and in non-English speakers (Mills et al, 2014;Sousa et al, 2015;Ahmad et al, 2017). Further, the goodness-of-fit findings parallel those reported for populations with varying characteristics (García-Campayo et al, 2012;Mills et al, 2014;Bartolo et al, 2017;Hinz et al, 2017;Rutter and Brown, 2017;Doi et al, 2018;Lee and Kim, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although the Tibetan PHQ-9 used here demonstrates acceptable reliability, it appears to have a lower alpha than has been found in other studies, many of which have yielded alpha levels above 0.80 (e.g. (20,22,25,(30)(31)(32)). The lower reliability may re ect something about the current translation, or it may re ect true differences in the way that symptoms are interpreted, experienced, or reported by this unique study population.…”
Section: Discussioncontrasting
confidence: 70%